PERENCANAAN IMPLEMENTASI UNIT KERJA REKAM MEDIS UNTUK KLINIK PRATAMA PANCASILA BATURETNO WONOGIRI - Anggia Meianti; Hendra Rohman; Anna Mayretta (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Health services in Pratama Pancasila Clinic Baturetno City Wonogiri mostly receives post partum and children case patients. Activities of medical record work unit has not been managed optimally. The management has a plan to change the system. In medical record work units, personnel are not qualified, organizing has not yet been established, operational standards are missing, decentralized storage systems, duplicate files, double entry data, and diagnostic coding not avaliable. The purpose of this studywas to design the initial concept of medical record work unit for pratama clinic. Qualitative descriptive research type. Population 25 people, sample 3 people. Data collection using observation and interview guidelines. The results showed that medical record management required qualified personnel with D3 medical recordsbackground, the creation of procedures from registration to reporting, storage systems shifted to centralization, thus minimizing file duplication, access rights to medical records, and coding according to ICD rules. The conclusion is that the initial concept of the medical record work unit for the primary clinic can be started from planning gradually from identification to alternative selection to be implemented according to standards and needs.